2019
DOI: 10.3390/su11236828
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Optimized Cleaner Production Strategies to Improve Water Environment and Economic Development in Leather Industrial Parks: A Case Study in Xinji, China

Abstract: The leather industry has contributed significantly to economic development, but serious water environmental problems have arisen due to manufacturing processes in this industry. The leather industry must implement sustainable development by improving cleaner production capabilities under the Chinese ecological development background. The Xinji industrial park in China has the largest leather production base in which the leather industry is the leading industry that contributes nearly 50% of economic gains. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Similarly, Selvaraj et al (2019) discovered the potential use of fleshing waste derived nanofibers as a sound absorbing layer in acoustic applications. Also, Gupta et al, (2018) revealed that tannery scraps and wastes could be recycled and upcycled into organic manures, useful for plantations while similar studies also explored waste management themes (Gerek et al, 2019;Kılıç et al, 2018;Li et al, 2019;Raghava Rao et al, 2003). These studies provide examples that demonstrate the practical uses of tannery generated wastes to derive significant value, while ensuring optimum environmental performance of tanneries.…”
Section: Themes Relating To the Environmental Dimensionmentioning
confidence: 99%
“…Similarly, Selvaraj et al (2019) discovered the potential use of fleshing waste derived nanofibers as a sound absorbing layer in acoustic applications. Also, Gupta et al, (2018) revealed that tannery scraps and wastes could be recycled and upcycled into organic manures, useful for plantations while similar studies also explored waste management themes (Gerek et al, 2019;Kılıç et al, 2018;Li et al, 2019;Raghava Rao et al, 2003). These studies provide examples that demonstrate the practical uses of tannery generated wastes to derive significant value, while ensuring optimum environmental performance of tanneries.…”
Section: Themes Relating To the Environmental Dimensionmentioning
confidence: 99%
“…, 2018) can be mentioned. In the leather industry, Li et al. (2019) highlight several sources of these impacts, such as the use of toxic substances, high water consumption and high water pollution levels.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is not wholly a new phenomenon with increasing levels of nutrients, accompanied by decreasing populations of fish and other aquatic species, seen across the UK since the industrial revolution (Bell et al, 2021). Indeed, the convergence of increasing development and reducing environmental quality, particularly water quality, has been observed around the world with examples including China (Rasiah et al, 2013;Xu and Berck, 2013;Han et al, 2017;Li et al, 2019), USA (Lozano et al, 2021) and France (Thiebault et al, 2021). In the UK improvements have been observed since the start of the 1900s with the introduction of wastewater treatment requirements and, more recently, regulations on the use of phosphorus in detergents (Naden et al, 2016) and the introduction of the Urban Wastewater Treatment Directive (Directive 91/271/EEC, 1991) and Water Framework Directive (Directive 2000/60/EC, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Globally 70% of consumptive water use is for agricultural irrigation (Wada et al, 2011;Zhao et al, 2020) and within the USA ∼82% of all water use is for agriculture and thermoelectric power generation (Luby et al, 2018). Competition and prioritization of water resources between different users is therefore a complex issue within which there is a wealth of research-see for example Gurluk and Ward (2009), Piniewski et al (2014), Kumar et al (2016), Wada et al (2017), Ahmadi et al (2020), Tomlinson et al (2020)including the consideration of separate water sources for different uses (United Kingdom Water Partnership, 2015; Oteng-Peprah production and sustainable development in China (Song et al, 2018;Li et al, 2019) aim to provide protection through legal obligation, although there are concerns that this is neither sufficient, nor quick enough, to improve the water quality in our lakes, rivers and seas (Lozano et al, 2021;Environment Agency, 2022). Additionally water protection and availability is not universal: around the world 2.2 billion people do not have access to clean drinking water and 4.2 billion people do not have access to safely managed sanitation (United Nations, 2015).…”
Section: Introductionmentioning
confidence: 99%